2020
DOI: 10.1016/j.jctb.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The (theta, wheel)-free graphs Part III: Cliques, stable sets and coloring

Abstract: A hole in a graph is a chordless cycle of length at least 4. A theta is a graph formed by three paths between the same pair of distinct vertices so that the union of any two of the paths induces a hole. A wheel is a graph formed by a hole and a node that has at least 3 neighbors in the hole. In this series of papers we study the class of graphs that do not contain as an induced subgraph a theta nor a wheel. In Part II of the series we prove a decomposition theorem for this class, that uses clique cutsets and 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Lemma 2.6 (Lemma 2.10 in [21]) Let G be a graph from D. Let (X 1 , X 2 ) be a 2-join of G, and G 1 , G 2 the blocks of decomposition with respect to this 2-join whose marker paths are of length at least 2. Then G 1 and G 2 are in D and they do not have star cutsets.…”
Section: Decomposing With 2-joinsmentioning
confidence: 99%
“…Lemma 2.6 (Lemma 2.10 in [21]) Let G be a graph from D. Let (X 1 , X 2 ) be a 2-join of G, and G 1 , G 2 the blocks of decomposition with respect to this 2-join whose marker paths are of length at least 2. Then G 1 and G 2 are in D and they do not have star cutsets.…”
Section: Decomposing With 2-joinsmentioning
confidence: 99%
“…This will be discussed in more details in Section 4. Lemma 2.6 (Lemma 2.10 in [21]) Let G be a graph from D. Let (X 1 , X 2 ) be a 2-join of G, and G 1 , G 2 the blocks of decomposition with respect to this 2-join whose marker paths are of length at least 2. Then G 1 and G 2 are in D and they do not have star cutsets.…”
Section: Decomposing With 2-joinsmentioning
confidence: 99%
“…In [25] it is shown that one can decompose a graph with no star cutset using a sequence of 'non-crossing' 2-joins into graphs with no star cutset and no 2-join (which will in our case be basic). In this paper we will use minimally-sided 2-joins (as opposed to [25] and [21], where minimally-sided 2-joins were 'moved' to allow marker paths to be disjoint). This will be particularly important when solving the induced paths problem.…”
Section: Remark 28mentioning
confidence: 99%
See 1 more Smart Citation
“…It remains open whether or not there is a polynomial χ-bounding function for graphs with no induced theta. The class of graphs with no induced theta or wheel has χ-bounding function max{ω, 3} [10] (where ω is the size of the largest complete subgraph).…”
Section: Introductionmentioning
confidence: 99%